Occupational Therapy Acute Care Self-Efficacy Scale (OTACSES): Development, Test–Retest Reliability, and Precision - Corey McGee; Hannah Oldenburg (Occupational Therapy International)
Discussion: The OTACSES is a reliable and precise tool for measuring students’ self-efficacy in the acute care setting. We present preliminary data on clinically meaningful change. Further research focusing on the tool as an outcome measure of the efficacy of acute care-relevant OT education and its appropriateness for use among practitioners is needed.